Photoluminescence tuning and energy transfer process from Tb3+ to Eu3+ in GPTMS/TEOS–derived organic/silica hybrid films - de Vicente, F. S. [UNESP]; Freddi, P. [UNESP]; Otuka, A. J.G.; Mendonça, C. R.; Brito, H. F.; Nunes, L. A.O.; Vollet, D. R. [UNESP]; Donatti, D. A. [UNESP] (Elsevier, 2018)
In this work the photoluminescence study and energy transfer from Tb3+ to Eu3+–β–diketonate complexes incorporated into organic/Silica hybrid films derived from 3–glycidoxypropyltrimethoxysilane (GPTMS) and tetraethylorthosilicate (TEOS) alkoxysilanes were investigated. Highly homogeneous and transparent films of Ln3+–doped GPTMS/TEOS–derived organic/silica hybrids were obtained from the organic/silica sols prepared by sol–gel. Tb3+:Eu3+–doped GPTMS/TEOS–derived films showed very intense luminescence when excited with UV light. Films co–doped with Tb3+ concentration fixed at 40.0×1018 ions/cm3 and Eu3+ concentrations of 0, 0.03, 0.05, 0.1, 0.3, 0.5, 1.0, 1.5, and 2.0×1018 ions/cm3 were studied. The films presented characteristic transitions 5D4–7F6-3 of Tb3+ ions and 5D0–7F0–4 of Eu3+ ions measured on the visible spectrum region. Energy transfer from Terbium to Europium was studied through emission decay time measurements of 5D4–7F5 transition of Tb3+ (547 nm) which showed an accentuated decrease (from 1329 to 55 µs) due to the co–doping with Eu3+ ions concentrations varied from 0.03 to 1.5×1018 ions/cm3. Energy transfer rate (WET) of 17.4×103 s−1 and relative energy transfer efficiency (ηT) of 96% were observed for films samples co–doped with 40×1018 ions/cm3 of Tb3+ and 1.5×1018 ions/cm3 of Eu3+. Due to the variation in WET and ηT from Tb3+ to Eu3+, the intensity ratios of Tb3+ band at 547 nm (5D4–7F5) and Eu3+ band at 617 nm (5D0–7F2) vary remarkably making the co–doped film samples exhibit different luminescence colors varying from green to orange and red which can be tuned by the Tb3+/Eu3+ ratio incorporated into the samples.